Atmospheric gas-particle partitioning versus gaseous/particle-bound deposition of SVOCs: Why they are not equivalent. (August 2015) - Glüge, Juliane; Bogdal, Christian; Scheringer, Martin; Hungerbühler, Konrad
Abstract: Semi-volatile organic compounds (SVOCs) can be particle-bound or in the gas phase in the atmosphere, depending on the (temperature dependent) gas-particle partitioning of the chemicals and the fraction of particles in air. Several studies linked gas-particle partitioning of SVOCs in the atmosphere directly to the gaseous/particle-bound deposition of these chemicals, i.e. in cases of compounds occurring mainly in the gas phase, the deposition was also assumed to be mainly in gaseous form. In this study, we apply a multi-media fate model to point out that gas-particle partitioning of SVOCs in air and gaseous/particle-bound deposition of SVOCs are driven by different mechanism and, thus, cannot be deduced from each other. We apply our calculations to polychlorinated biphenyls (PCBs), as model SVOCs. We show that the fraction of particle-bound deposition to deciduous forest is 1.5–190 times higher in winter and between 5 and 1000 times higher in summer than the particle-bound fraction of these chemicals in air. The fraction of particle-bound deposition to coniferous forest is 1.5–172 times higher in winter and between 5 and 1000 times higher in summer than the particle-bound fraction of PCBs in air. In addition to the fractions of particle-bound SVOCs in air and particle-bound deposition, we recalculated particle-bound and gaseous deposition velocities to coniferous and deciduous forest for PCBs. The deposition velocities obtained for dry gaseous deposition (<1 m/h) are much lower than the existing values in the literature (10–200 m/h) because earlier studies assumed that for PCBs occurring predominantly in the gas phase, interception was also completely due to dry gaseous deposition. Highlights: Gas-particle partitioning vs. gaseous/particulate deposition of SVOCs. Calculating deposition velocities to forest with varying seasonal deposition fluxes. Particle-bound and gaseous deposition velocities for PCBs to two different canopies.